1, 1,6-Trimethyl-1,2-dihydronaphthalene (TDN): A Possible Degradation Product of Lutein and beta-Carotene - Marais, J. (South African Journal of Enology and Viticulture, 2017)
Lutein and beta-carotene were heated in H2S04 and ethanol/tartaric acid media adjusted to pH 1 and 3, respectively. Various products were formed, but 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN), responsible for the kerosene-like flavour of aged Weisser Riesling wines, derived from lutein only.